Health Education In Increasing Self-Efficacy In The Treatment Of Tuberculosis Patients At Tamalanrea Makassar Health Center - Yasir Haskas; Sriwahyuni Sriwahyuni; Muh. Chandra Adhitya Fairil (Pusat Riset dan Inovasi Nasional, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis which spreads through the air (Airborne disease).symptoms of cough with phlegm for 2 weeks or more.Disease prevalenceTB (Tuberculosis)as many as 845,000 with a death rate reaching 98,000 cases, treatment coverage is only 67%, several factors cause unhealthy housing, education and non-compliance with treatment inutritional indicators, immune levels, greatly influence the quality of life of tuberculosis sufferers so that there is a need to increase self-efficacy in managing the disease,with education about the infectious disease tuberculosis The research method used was pre-experimental with a one group pre-test and post-test design with a sample size of 36 people. The instrument we used was a pre- and post-questionnaire and provided intervention in the form of health education. The results of the research showed that after health education was carried out, the Negative Ranks data showed that respondents' scores from pre-post 3 respondents experienced a decrease in self-efficacy regarding tuberculosis treatment after health education, while the positive ranks data showed that 12 respondents' scores from pre-post experienced an increase. Self-efficacy towards tuberculosis treatment after health education, and the tie data shows that 21 respondents got a fixed score from pre-post after health education. The results of the Wilcoxon statistical test obtained a p value = (0.020) <α (0.05), and so The alternative hypothesis (Ha) is accepted. The conclusion is that there is an influence of health education on increasing self-efficacy in the treatment of tuberculosis sufferers at the Tamalanrea Makassar Community Health Center